The implications of the nominal sentence in the legislative verses in the Quranic story - Mustafa Mohammed Salman; Dr. Qusay Jawad Al-Ghrawi (Journal of College of Education, 2024)
There is no doubt that the legitimacy of a special place is clear within the Islamic community, as it contributes to and influences the souls of all Muslim men and women. It is responsible for everything that is done by individuals, whether good or bad, and Sharia, whether in action, speech, or report, is considered to be the driver. It was established. All members of the Islamic community are its members and they are influenced by it and do what it urges them to do and end with what it forbids them. Whoever intends to apply it in this world has achieved his goal in his afterlife. Sharia is what the individual applies with all its commands and prohibitions. He is guaranteed his afterlife, and whoever deviates from Sharia has perished.